Case report: First case of pemetrexed plus cisplatin-induced immune hemolytic anemia in a patient with lung adenocarcinoma - Lu, Hongkai; Wang, Na; Wang, Peng; Zhang, Haolin; Zhao, Ru; Liu, Hongju; He, Xirong; Liu, Zeya; Chang, Yue; Cao, Yongtong; Wang, Shiyao (Frontiers in Medicine, 2022)
Background: Drug-induced immune hemolytic anemia (DIIHA) is rare, but potentially life-threatening. No DIIHA has been reported with pemetrexed plus cisplatin as a first-line chemotherapy regimen for advanced stage non-small cell lung cancer. Case presentation: In this report, a patient with advanced stage lung adenocarcinoma developed severe immune hemolytic anemia 21days after pemetrexed plus cisplatin chemotherapy. Laboratory parameters were consistent with severe hemolysis, including the rapid decline of hemoglobin, elevation of reticulocytes, indirect bilirubin and lactate dehydrogenase. A workup for possible DIIHA was performed, including direct antiglobulin test (DAT), testing of drug-treated red blood cells (RBCs), and testing in the presence of soluble drug. It showed strong positive (3+) results for anti-C3d, but not anti-IgG in DAT. Enzyme-treated RBCs weakly reacted with patient's serum and pemetrexed when complement was added. The patient's serum and normal sera were reactive with cisplatin-treated RBCs. But the eluate from the patient's RBCs and diluted normal sera were nonreactive with cisplatin-coated RBCs. Both untreated and enzyme-treated RBCs reacted with patient's serum in the presence of soluble cisplatin. In vitro serological tests suggested that complement-dependent pemetrexed antibodies and a non-immunologic protein adsorption (NIPA) of cisplatin may elicit immune hemolytic anemia. Anemia improved when pemetrexed and cisplatin were discontinued. Conclusion: The patient with DIIHA was demonstrated to have complement-dependent pemetrexed antibodies. Cisplatin was shown to cause NIPA. The complement-dependent pemetrexed antibodies and /or the cisplatin-induced NIPA could have contributed to the patient's hemolytic anemia.